Effect mobile learning application in children’s interest - Siti Hasnah Tanalol; Aslina Baharum; Magrizef Gasah; Nadiah Hanin Nazlan; Noorsidi Aizuddin Mat Noor; Salinah Dullah (Pennwell Corporation, 2020)
Mobile learning application is a teaching aid that can help students to self-study with or without guidance. Unfortunately, the mobile learning application did not help in identifying the increase in students' interest in learning especially children. This paper will discuss how mobile learning application affect the children interest in learning. Mix method of qualitative and quantitative used to evaluate the children interest based on the assessment score, micro-expression (facial expression) and interview. The results from all of the three methods show a positive interest are exist among children.